EFEMP1 is a potential biomarker of choroid thickness change in myopia - Shi, Wen-Qing; Wan, Ting; Li, Bing; Li, Tao; Zhou, Xiao-Dong (Frontiers in Neuroscience, 2023)
PURPOSE: To explore the possible molecular mechanism by which epidermal growth factor-containing fibulin-like extracellular matrix protein 1 (EFEMP1) regulates choroid thickness (CT) in the development of myopia. METHODS: One hundred and thirty-one subjects were divided into the emmetropia (EM) group, nonhigh myopia (non-HM) group and high myopia (HM) group. Their age, refraction, intraocular pressure, and other ocular biometric parameters were collected. A 6*6 mm area centered on the optic disc was scanned by coherent optical tomography angiography (OCTA) to measure CT, and the tear concentrations of EFEMP1 were quantified using enzyme-linked immunosorbent assay (ELISA) analysis. Twenty-two guinea pigs were divided into the control group and the form-deprivation myopia (FDM) group. The right eye of the guinea pig in the FDM group was covered for 4 weeks, and the diopter and axial length of the right eye of the guinea pig were measured before and after the treatment. After the measurement, the guinea pig was euthanized, and the eyeball was removed. Quantitative reverse transcription polymerase chain reaction ,western blotting assays and immunohistochemistry were used to assess the expression of EFEMP1 in the choroid. RESULTS: There were significant differences in CT among the three groups (p<0.001). CT was positively correlated with age in HM (r=-0.3613, p=0.0021), but no significant correlation with SE (p>0.05) was observed. Furthermore, there were increased levels of EFEMP1 in the tears of myopic patients. After 4 weeks of covering the right eye of the FDM guinea pigs, there was a significant increase in axial length and a decrease in diopter (p<0.05). The mRNA and protein expression of EFEMP1 was significantly increased in the choroid. CONCLUSION: Choroidal thickness was significantly thinner in myopic patients, and the expression level of EFEMP1 in the choroid increased during the development of FDM. Therefore, EFEMP1 may be involved in the regulation of choroidal thickness in myopia patients.